The impact of pre-injury controlled substance use on clinical outcomes after trauma. Issue 5 (November 2016) - Cheng, Vincent; Inaba, Kenji; Johnson, Megan; Byerly, Saskya; Jiang, Yue; Matsushima, Kazuhide; Haltmeier, Tobias; Benjamin, Elizabeth; Lam, Lydia; Demetriades, Demetrios
Abstract : BACKGROUND: A disproportionately high percentage of trauma patients use controlled substances, and they often co-ingest multiple drugs. Previous studies have evaluated the effect of individual drugs on clinical outcomes after trauma. However, the impact of all drugs included in a comprehensive screening panel has not yet been compared in a single cohort of patients. METHODS: All trauma patients who underwent urine drug screens after admission to the LAC + USC Medical Center (January 2008–June 2015) were identified retrospectively. Univariable and multivariable regression analyses determined the significance of all drugs tested in the hospital's standard toxicology screen (amphetamine, barbiturate, benzodiazepine, cocaine, opiate, phencyclidine) on clinical outcomes. RESULTS: A total of 10, 166 patients who underwent admission toxicology screening were identified. Although 5, 621 patients had completely negative screens, 3, 292 patients tested positive for only one drug and 1, 253 patients tested for multiple drugs. Univariable analysis indicated that patients who tested positive for multiple drugs had higher rates of operative intervention ( p < 0.001), longer hospital stay ( p < 0.001), and longer ICU stays ( p < 0.001). Multivariable analysis indicated that phencyclidine was associated with higher rates of mortality ( p = 0.025) whereas amphetamine was associated with lower rates of mortality ( p = 0.012). Higher rates of operative intervention were observed in patients testing positive for amphetamine ( p < 0.001), benzodiazepine ( p < 0.001), or opiate ( p < 0.001). Benzodiazepine use was associated with higher rates of mechanical ventilation ( p < 0.001), but use of amphetamines ( p = 0.021) or opiates ( p < 0.001) was associated with lower rates. CONCLUSIONS: Pre-injury use of amphetamine, barbiturate, benzodiazepine, cocaine, opiate, and PCP has a significant and variable impact on clinical outcomes after trauma. Comparing the relative effect of each drug class can help clinicians risk-stratify all trauma patients, including those who test positive for multiple substances. LEVEL OF EVIDENCE: Epidemiologic study, level III.